Innovative approaches to design and production automation - Vodianytskyi, Ivan; Водяницький, Іван Олексійович (Запоріжжя: ТДАТУ, 2026)
Modern industrial development is characterised by a high level of digitalisation and requires the introduction of automated systems in all areas of production. Traditional approaches to product design and manufacturing no longer deliver the speed, accuracy, and flexibility required. 3D design and visualisation are gaining particular importance, having become an integral part of creating promising design and engineering solutions. The issue of integrating engineering methods and tools arises as engineers simultaneously address the shortage of qualified engineers. The key to efficiency today lies in having professional tools and organising coordinated teamwork within a single digital space.
Keywords: automated systems; teamwork